NASAF AS A CENTER OF LEARNING: HISTORICAL FOUNDATIONS, KNOWLEDGE PRODUCTION, AND INTELLECTUAL LEGACY IN MAWARANNAHR (International Congress on Economics, Management and Business Studies, 2026)
This article examines Nasaf as one of the important intellectual centers of Mawarannahr and analyzes its role in the formation, preservation, and transmission of knowledge in the medieval Islamic world. The study argues that Nasaf’s scholarly significance emerged from the interaction of its deep urban-historical roots, its location within the cultural geography of southern Sogdiana, and its integration into the broader religious and intellectual networks of Transoxiana. Special attention is given to the contributions of Abu al-Mu'in al-Nasafi, Najm al-Din Umar al-Nasafi, and Aziz Nasafi, whose works in kalam, theology, historiography, and Sufi thought reflect the diversity and maturity of the Nasaf scholarly tradition. The article concludes that Nasaf should be understood not merely as a provincial city of the past, but as an enduring center of Islamic learning whose legacy remains relevant to the study of Central Asian civilization, intellectual history, and the modern rediscovery of the region’s spiritual heritage.
Keywords: Nasaf; Nakhshab; Mawarannahr; Transoxiana; Islamic scholarship; Maturidism; Abu al-Mu'in al-Nasafi; Umar al-Nasafi; Aziz Nasafi; intellectual history.